Responsible FDI is no longer optional - Roel Nieuwenkamp (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2018)
Responsible foreign direct investment is no longer optional, but morally binding. The OECD Guidelines for Multinational Enterprises and its global system of responsible business authorities provides concrete examples of this trend. Increasingly, hard consequences are attached by governments and investors to non-compliance with international standards on responsible business conduct.
Keywords: 330